The Analysis of the Decisions of the Sharia Court Judges on Child Rape Cases in the City of Langsa - Muzakkir, Muzakkir (Institut Agama Islam Negeri Curup, 2022)
This study analyzes of the Decisions of the Sharia Court Judges on Child Rape Cases in the City of Langsa Number 33/JN/2021/MS.Lgs, which gave a prison sentence for perpetrators of raping biological children, this type of research is qualitative using empirical normative legal methods (application) that will analyze the written law and apply it at the time of the case. Research is a type of normative research using a case approach; the primary data source is in the form of a first-level decision that was tried by the Mahkamah Syar’iyah of Langsa City Number 33/JN/2021 /MS.Lgs, as for the research findings, the judge gave a decision based on the Qanun Jinayat with a fine of 165 months in prison because the victim in his request to be tried by the Qanun jinayat. The things that burden the uqubat for the perpetrators are: The defendant's actions did not support the Aceh Provincial government's program in enforcing Islamic Shari'a in Aceh Province; The Defendant's actions caused anxiety and damaged the future of the Victim's Child; The defendant is the biological father of the victim's child who is supposed to protect and guide the victim's child; and while the mitigating factors for the perpetrator are that the defendant is polite at trial and has never been convicted.